2023
DOI: 10.3390/jpm13020276
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte/HDL Cholesterol Ratios as a New Inflammatory Marker in Patients with Schizophrenia

Abstract: Purpose: Monocyte/HDL cholesterol ratio (MHR) is a novel inflammatory marker that is used as a prognostic factor for cardiovascular diseases and has been studied in many diseases. The aim of this study was to investigate the role of inflammatory factors in schizophrenia patients by examining MHR levels and to compare schizophrenia patients and healthy controls in terms of cardiovascular disease risk. Method: A total of 135 participants between the ages of 18–65, 85 diagnosed with schizophrenia, and 50 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Another constellation of the root factor structure consists of three parameters of lipid peroxidation, with opposite signs. This situation is consistent with the current view of atherosclerosis as chronic low-grade inflammation and oxidative stress [9,14,21,25]. The presence of glycemia in the structure of the root as a component of the metabolic syndrome is quite understandable as well as AlT and γ-GTP as markers of cytolysis, which in turn is a consequence of oxidative stress.…”
Section: Table 5 Squared Mahalanobis Distances Between Lipids Cluster...supporting
confidence: 89%
“…Another constellation of the root factor structure consists of three parameters of lipid peroxidation, with opposite signs. This situation is consistent with the current view of atherosclerosis as chronic low-grade inflammation and oxidative stress [9,14,21,25]. The presence of glycemia in the structure of the root as a component of the metabolic syndrome is quite understandable as well as AlT and γ-GTP as markers of cytolysis, which in turn is a consequence of oxidative stress.…”
Section: Table 5 Squared Mahalanobis Distances Between Lipids Cluster...supporting
confidence: 89%
“…Furthermore, while elevated MLR may represent a shared pathological hallmark of SCZ and BD compared to HCs, some discrepancies remain, possibly related to methodological variations and differing patient inclusion criteria [70,71]. Similar relationships were observed between monocyte counts and other metabolic markers, such as the cardioprotective HDL (monocyte to HDL ratio, MHR), hinting at a possible involvement of these cells with the onset of cardiometabolic comorbidities in SCZ and BD [72][73][74][75]. These observations of alterations in various monocyte features represent a significant breakthrough in SCZ research.…”
Section: Monocytesmentioning
confidence: 85%
“…Monocytes Increased total monocyte counts [62][63][64] Increased classical monocyte counts [66] Increased pro-inflammatory monocyte counts [67] Increased monocyte to lymphocyte ratio [68] Increased monocyte to HDL ratio [72,73] Increased TREM1/2 [79,80] Increased ATF3/EGR3 [78] Increased HLA-DR [82] Increased phagocytosis [81] Increased IL-1, IL-6, TNF-α [83,85,86] Increased CD36 [93] Increased reactive oxygen species [92] Alterations in TLR4 signaling [84,87,88] Unique interferon gene signature [77] Reduced GLUT1 [89] Granulocytes Increased neutrophil counts [68,94-99] Increased neutrophil to lymphocyte ratio [100,101] Increased oxidative stress [108] Increased malonaldehyde [122] Increased superoxide anion [123,123] Increased phagocytosis [81,124] Natural killer cells Increased total counts [68] Decreased total counts [125][126][127] No change in total counts [128] Increased cytotoxicity [132] Decreased cytotoxicity [129,130] No change in cytotoxicity [121] Increased NKG2C [133] Increased S100B [134] Table 1. Cont.…”
Section: Peripheral Blood Featuresmentioning
confidence: 99%
“…The authors concluded that recommendations such as diet and exercise, in the treatment approaches might be beneficial in protecting schizophrenia patients against cardiovascular diseases and early death. 24…”
Section: Discussionmentioning
confidence: 99%